Adjuvant treatment combining cellular immunotherapy with chemotherapy improves the clinical outcome of patients with stage II/III gastric cancer. (27th October 2016) - Wang, Yizhuo; Wang, Chang; Xiao, Huijie; Niu, Chao; Wu, Haitao; Jin, Haofan; Yao, Cheng; He, Hua; Tian, Huimin; Han, Fujun; Li, Dan; Han, Wei; et al.
Abstract: Postsurgical relapse remains a common issue for resectable gastric cancer (GC). Here, we investigated the efficacy and safety of an adjuvant treatment combining chemotherapy with cellular immunotherapy (CIT) using autologous natural killer cells, γ δT cells, and cytokine‐induced killer cells in the treatment of stage II/III GC. A pilot prospective cohort study was conducted in 169 patients with stage II/III GC who had undergone gastrectomy with D2 lymph node dissection. Patients were assigned into two groups according to the patient choice of treatment, including chemotherapy alone (chemo) or chemotherapy combined with CIT (chemo/CIT). Disease‐free survival (DFS), overall survival (OS), and adverse events were evaluated. Univariate and multivariate Cox models were used to analyze the impact of chemo/CIT on DFS and OS. Kaplan–Meier analysis with the log‐rank test was used to compare the clinical outcome between two groups. Three‐year DFS rate was 60.6% and 74.7% ( P  =   0.036) and 3‐year OS rate was 64.9% and 83% ( P  =   0.051) for the chemo and chemo/CIT group, respectively. TNM stage and chemo/CIT were independent prognostic factors for both DFS (for TNM stage, P  <   0.001, hazard ratio [HR]: 5.599, 95% confidence interval [CI]: 2.791–11.232; for chemo/CIT, P  =   0.013, HR: 0.478, 95% CI: 0.266–0.858) and OS (for TNM stage, P  <   0.001, HR: 6.559, 95% CI: 2.903–14.817; for chemo/CIT, P  =   0.04, HR: 0.506, 95% CI: 0.264–0.970). In subgroup analysis, 3‐year DFS and OS rates of patients with stage III GC in the chemo/CIT group were significantly higher than those in the chemo group (38.4% vs. 57.1%, P  =   0.038; and 45.9% vs. 76%, P  =   0.06, respectively), while there was no significant difference between the two groups in patients with stage II GC. Only 15.9% of patients (10/63) in the chemo/CIT group had mild and manageable fever (grades 1 and 2), while no other side effects were observed. The adjuvant treatment combining chemotherapy with cellular immunotherapy is well tolerated and significantly improves the clinical outcome of patients with stage II/III GC, when compared with chemotherapy alone, therefore warrants further attention in treatment for relapsed GC after tumor resection. Abstract : The adjuvant treatment combining chemotherapy with cellular immunotherapy is well tolerated and significantly improves the clinical outcome of patients with stage II/III gastric cancer (GC), when compared with chemotherapy alone, therefore warrants further attention in treatment for relapsed GC after tumor resection.